Gerenciamento de resultados, tamanho da firma de auditoria e relatórios modificados: evidências em empresas listadas no mercado acionário brasileiro - Tommasetti, Roberto (2017)
Recent financial scandals focus public opinion on the concept of earning management and the importance of corporate governance tools, first of all audit and its main output: the audit opinion. The new auditing standard ISA 701, by introducing the KAMs (Key Communication Matters) into the audit opinion from December 2016 for listed company, underlines the need for a deeper communication between auditing and market, throught the audit report. This paper examines: (H1) the relationship between abnormal accruals, as proxi of earning management practices, and auditor size (AS) and (H2) wheather the presence of earnings management (EM) triggers the issuance of qualified or modified audit opinion (MAO), in order to gain a better understanding on the reliability of audit opinion in Brazil. Sample selection consists of a balanced Brazilian listed firms panel (financial sector excluded) during the period 2012-2015 for a total of 1,132 firms-years observations. First, we estimated earnings management through cross-sectional modified Jones model, as reviewed by Karniz first (1999) and Kothari after (2005). Then, we performed: (H1) a linear regression where absolute discretionary accruals variable (ADA) is the dependent and the auditor size the main independent and (H2) a logistic regression model in order to analyze the relation between audit qualification (binary dependent) and earnings management measure. As result from the first hypothesis, the (negative) relationship between ADA and AS, even statistically insignificant, would probably means that Big 4 auditor somehow inhibits the level of discretionary accruals. The main control variables strongly influencing the depedent are the leverage level (positively) and return on asset values (negatively). As result from the second hypothesis, there is a positive relationship between audit qualification and ADA. This means that when the company practices EM, auditor is more likely to render a qualified opinion. We tested this hypothesis under two modified opinion scenarios: in the first (MAO1), emphasis paragraph is considered as a qualification (lato sensu) while in the second (MAO2), only exeptions and adverse opinions are considered as a qualification (stricto sensu)